HTML5 for masterminds - Gauchat, J.D.; Colgan, Jessie (Vancouver : Mink Books, 2012)
HTML5 for Masterminds leads the reader step by step to gain essential knowledge and to master complex subjects included in the HTML5 specifications. After reading this book, you will know how to structure your documents with HTML5, how to style them with CSS3 and how to work with the most powerful Javascript APIs. This book is not an introduction of HTML5 but instead a complete course that will teach you how to build compelling websites and amazing web applications from scratch. Every chapter explores basic as well as complicated concepts of HTML5, CSS3 and Javascript. Information is supported by fully functional examples to guide beginners and experts through every single tag, style and function included in the specifications. The examples are distributed throughout the book in a specific order to gradually introduce complex subjects and make them accessible to everyone. The goal of HTML5 for Masterminds is to make you familiar with the most advanced technology for the web. It was developed to prepare you for the future, and it was written for the genius inside you... for Masterminds.
Chapter 1. HTML5 Documents -- Chapter 2. CSS Styling and Box Models -- Chapter 3. CSS3 Properties -- Chapter 4. Javascript -- Chapter 5. Forms and Forms API -- Chapter 6. Video and Audio -- Chapter 7. Text Track API -- Chapter 8. Fullscreen API -- Chapter 9. Stream API -- Chapter 10. Canvas API -- Chapter 11. WebGL and Three.js -- Chapter 12. Pointer Lock API --Chapter 13. Drag and Drop API -- Chapter 14. Web Storage API -- Chapter 15. IndexedDB API -- Chapter 16. File API --Chapter 17. Geolocation API -- Chapter 18. History API -- Chapter 19. Offline API -- Chapter 20. Page Visibility API -- Chapter 21. Ajax Level 2 -- Chapter 22. Web Messaging API -- Chapter 23. WebSocket API -- Chapter 24. WebRTC API -- Chapter 25. Web Audio API -- Chapter 26. Web Workers API -- Conclusion
Includes index.
Keywords: HTML (DOCUMENT MARKUP LANGUAGE)